Magnésio, cálcio e potássio em sementes e cotilédones de feijoeiros e sua transferência para plantas jovens - Boaro, Carmen Sílvia Fernandes; De Moraes, Jose Antonio Proenca Vieira; Rodrigues, João Domingos [UNESP]; Ono, Elizabeth Orika; Pedras, José Figueiredo [UNESP]; Curi, Paulo Roberto [UNESP] (My University, 1998)
Magnesium, calcium and potassium concentration in the seeds and cotyledons of Phaseolus vulgaris L. cv. Carioca and its translocation from the cotyledons to the plant were evaluated. For such an evaluation plants were cultivated during the cotyledons phase and were irrigated with deionized water. Three samplings of cotyledons completely randomized were done and replicated ten times, before its senescence and fall, at 8, 12 and 15 days after the germination of the seeds. Fresh and dry matter of the cotyledons and its magnesium, calcium and potassium content were determinated in every sample. These parameters were also determined in the seeds from the same lot. Potassium concentration was higher than magnesium in both seeds and cotyledons. Calcium presented the lesser concentration both in seeds and cotyledons. These minerals were translocated from the seeds and cotyledons to the young plants. Eight days after germination 59% of the magnesium, 78% of the calcium and 71% of the potassium were translocated to the plants. Fifteen days after germination these percentages were respectivaley 73%, 82% and 91%. Thus, magnesium was the less and potassium was the most translocated mineral at the end of the study.

O presente estudo objetivou avaliar os teores de magnésio, cálcio e potássio em sementes e cotilédones do feijoeiro (Phaseolus vulgaris L. cv. Carioca) e a transferência desses minerais dos cotilédones para a planta. Para tanto, plantas de feijão foram cultivadas durante a fase de existência dos cotilédones e irrigadas com água desmineralizada. Foram realizadas três colheitas dos cotilédones das plantas jovens, escolhidas ao acaso de dez repetições, antes da ocorrência de senescência e queda, aos 8, 12 e 15 dias após a germinação das sementes. Em cada colheita, determinaram-se as matérias fresca e seca dos cotilédones e teores de magnésio, cálcio e potássio. Esses parâmetros também foram avaliados em sementes retiradas do mesmo lote. Os resultados demonstraram que o potássio existe nas sementes e cotilédones em maior teor, seguido, em ordem decrescente, pelo magnésio e cálcio. Na 1a colheita dos cotilédones, realizada oito dias após a germinação, 59% de magnésio, 78% de cálcio e 71% de potássio já tinham sido transferidos para as plantas. Na última colheita, realizada 15 dias após germinação, essas porcentagens eram de 73%, 82% e 91%, respectivamente. Desta forma, o mineral menos transferido foi o magnésio, e o mais translocado, o potássio.
Magnesium, calcium and potassium in seeds and cotyledons of common bean and its translocation to the young plants
Keywords: Cotyledon reserve; Macronutrients; Phaseolus vulgaris; Seminal reserve; Phaseolus (angiosperm)